Peningkatan Kemampuan Orang Tua Dalam Pengasuhan Anak - Zulfahmi Zulfahmi; Ricca Angreini; Saipul Alsukri; Rudiadi Rudiadi; Adi Kurniawan (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
The pattern of parenting in children is a description of the behavior of parents in educating, paying attention to what will ultimately be felt by children. Parenting is the key to how a quality Indonesian generation will be born in the future. For this reason, in order to support the ability of parents in caring for children, community service is carried out with the topic of Increasing the Ability of Parents in Parenting Children Facing Millennial Generation in East Sidomulyo Village, Pekanbaru City. This service provides a significant change (post-test results) in the knowledge of the mothers of Pkh members in the parenting pattern of their children. This can be seen from the Dysfunctional Parenting scale which moves from high dysfunctional parenting to low dysfunctional parenting.